Dampak Perubahan Harga BBM Terhadap Biaya Operasional Supir Truck Antar Kota dan Provinsi - Suyatin, Febri Ramahdansyah, LCA. Robin Jonathan (EKONOMIA, 2016)
This study aims to determine and analyze the effects of changes in the price of fuel (fuel oil) to the truck driver Operational costs. Formulation of the problem is whether the impact of changes in fuel prices (fuel oil) significantly affects the operational expenses of truck drivers among cities and provinces. The hypothesis in this study is: